2022
DOI: 10.1101/2022.08.08.22278542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is the self-reporting of mental health problems sensitive to public stigma towards mental illness? A comparison of time trends across English regions (2009-19)

Abstract: Purpose. The prevalence of mental health problems has rapidly increased over time. The extent to which this captures changes in self-reporting due to decreasing stigma is unclear. We explore this by comparing time trends in mental health and stigma-related indicators across English regions. Methods. We produced annual estimates of self-reported mental disorders (SRMDs) across waves of the Health Survey for England (2009-18, n = 78,226) and three stigma-related indicators (knowledge, attitudes, and intended b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The extent to which time trends in public stigma and mental health are related, however, remains unclear, with at least one study finding no overlap between changes in stigma-related indicators and self-reported mental disorders across English regions over the past decade. 10 Part of the problem in disentangling this mechanism concerns the different levels at which stigma operates, and the extent to which each of these may affect self-reporting. 11 A number of studies examined the variability of stigma-related indicators and mental health problems in England and found that while the local and regional levels may not have a substantive role, the household level may influence the relationship between stigma and self-reporting to a meaningful extent.…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which time trends in public stigma and mental health are related, however, remains unclear, with at least one study finding no overlap between changes in stigma-related indicators and self-reported mental disorders across English regions over the past decade. 10 Part of the problem in disentangling this mechanism concerns the different levels at which stigma operates, and the extent to which each of these may affect self-reporting. 11 A number of studies examined the variability of stigma-related indicators and mental health problems in England and found that while the local and regional levels may not have a substantive role, the household level may influence the relationship between stigma and self-reporting to a meaningful extent.…”
Section: Introductionmentioning
confidence: 99%